The Effect of Bankruptcy Possibility on Audit Delay and Timeliness (Empirical Study on Manufacturing Companies Listed in Indonesian Stock Exchange in the Period of 2012-2016) - Triana Meinarsih; Abdul Yusuf; Muhammad Zilal Hamzah (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2018)
Audit delay and timeliness are important factors that influence the quality of accounting information in term of relevance. This study provides empirical evidence to answer the question of how bankruptcy possibility impacts on audit delay and timeliness.  This research studies manufacturing firms listed in Indonesian Stock Exchange (IDX) in the period of 2012-2016. Data are taken from official website of IDX. This study is a quantitative research that seek to find out relationship between independent variable and dependent variable. External secondary data used are annual reports accessed from IDX website. Measurement used is Z-Score Altman model prediction, while simple linear regression is employed as technical analysis. This study finds that bankruptcy possibility which is measured by ZScore is negatively influence audit delay and timeliness. Any decrease of Z-Score shows the possibility of a company experience bankruptcy and therefore causes audit delay and timeliness.